Peningkatan Ketrampilan Metakognisi Mahasiswa IKIP Budi Utomo Malang Melalui Penerapan Tutor Sebaya Dipadukan dengan The Power of Two dalam Matakuliah Kimia Dasar - Wilyati Agustina (IKIP Budi Utomo Malang, 2019)
Based on the observation showed that the student’s do not use the concept they had to solve new problems that is solved by using they had. The basic chemical is general courses that must be taken by students of MIPA (Mathematics and Science), where subjects are abstract and difficult to understand, the calculation of the chemical needs to optimize the students’ ability, it is expected to be able to form: independent personality, patterned science thought, creative, and an objective that has a character (soft skills) in appearance , attitude, and behavior levels. One of the parameters to find out is through the skill improvement metacognition. In the reserach problem is wether peer teaching merged with the power of two in The basic chemical can improve IKIP Budi Utomo student’smetacognitive skill. The design of this reserch is Class action reserach that developed by Kemmis and Taggart. There are four steps/ phases. 1) planning, 2) acting, 3) observing, 4) analyzing and reflecting. The result of study reserach, there is significant improvement from the average of cicle I to II from 44,5 score- 69,3 and the score of completness is 40,3 %